2017
DOI: 10.1177/0363546517697302
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Preoperative Extrusion of the Medial Meniscus and Surgical Outcomes After Partial Meniscectomy

Abstract: The preoperative extent of intrameniscal degeneration and the preoperative patterns of meniscal tear including horizontal, horizontal flap, and complex tears were associated with preoperative extrusion of the medial meniscus. The preoperative extrusion of the medial meniscus was negatively correlated with outcomes of partial meniscectomy. The preoperative extent of meniscal extrusion can be used as a predictive factor for osteoarthritis in partial meniscectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 33 publications
2
43
2
Order By: Relevance
“…In addition to the initial pain and disability from meniscus injury, approximately 50% of patients with a meniscus tear will develop osteoarthritis within 10-20 years following injury [1,5,9,10]. Total or partial meniscectomy is frequently performed to reduce pain and mechanical symptoms but has been strongly associated with the subsequent development of osteoarthritis [11][12][13]. Despite this, partial meniscectomy remains one of the most commonly performed orthopaedic procedures [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the initial pain and disability from meniscus injury, approximately 50% of patients with a meniscus tear will develop osteoarthritis within 10-20 years following injury [1,5,9,10]. Total or partial meniscectomy is frequently performed to reduce pain and mechanical symptoms but has been strongly associated with the subsequent development of osteoarthritis [11][12][13]. Despite this, partial meniscectomy remains one of the most commonly performed orthopaedic procedures [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…Meniscal extrusion is characterized by the displacement of the meniscus beyond the tibial margin. 17,19,23,26 Meniscal root tear, bucket-handle meniscal tear, joint space narrowing, and medial collateral ligament (MCL) injury may be among the causes of meniscal extrusion. 1,7,21 A symptomatic meniscal extrusion is more frequent in the medial meniscus, measuring more than 3 mm at the midlevel of the MCL.…”
mentioning
confidence: 99%
“…14 Yet, the meniscal extrusion cutoff points for unsatisfactory clinical outcomes in the present study are lower than the most adopted cutoff point of 3 mm found in the literature, which has been considered as pathological 4,13,25,26 and associated with large meniscal degeneration 13 and with radiographic progression of osteoarthritis. 14,[27][28][29] When comparing the cutoff point of 2.2 mm for predicting unsatisfactory Lysholm score postoperatively and the most adopted cutoff of 3 mm, of the 16 patients in this study that had meniscal extrusion between 2.2 and 3.0 mm, 50% of them had unsatisfactory (poor or fair) Lysholm scores. These patients would not be considered with pathological meniscal extrusions preoperatively if the cutoff point 3.0 mm was used, leaving a significant number of patients out of the risk group for unsatisfactory clinical outcomes.…”
Section: Discussionmentioning
confidence: 87%